The Role of Hormonal changes in Recurrent Urinary Tract Infections among Postmenopausal Women. A Clinical Perspective Study - Sadia Bint Karim, Ghulam Mustafa, Asma Jabeen, Parveen Azam, Ibtisam Nawaz Minhas, Saba Zafar, (Pakistan Journal of Medical & Health Sciences, 2023)
Aims and Objectives: The objectives of the study were to understand the urinary tract infections (UTIs) and their importance in postmenopausal women, associated with estrogen deficiency, alterations in vaginal microbiota and urogenital susceptibility. Methodology: The role of hormonal and non-hormonal interventions in reducing UTI recurrence was tested in a prospective multicenter cohort. Six hundred postmenopausal women were stratified into three groups: hormone replacement therapy (HRT), non-hormonal interventions (e.g., probiotics, D-mannose), and a control group. Demographic, clinical history, biomarkers and outcomes were analyzed. Results: Results showed a 45% and 38% reduction in UTI recurrence rates for HRT and non-hormonal groups compared to controls. Intervention groups showed improved lactobacillus abundance and vaginal pH, improved quality of life. These findings highlight how these interventions are effective in management of recurrent UTIs without adverse effects on antimicrobial resistance. Given this, further research is recommended to investigate long term efficacy and to integrate behavioral factors to promote comprehensive prevention strategies. Conclusion: Interventions, both hormonal and non-hormonal, including hormone replacement therapy, probiotics, and D-mannose, substantially decrease recurrent UTIs in postmenopausal women and address concerns about antimicrobial resistance. These findings underscore the need for individualized, preventive strategies to promote clinical outcomes and quality of life. Keywords: Hormone, Urinary tract infection, Postmenopausal, Antimicrobial, Probiotics.